Big Bros Chicken / Wan Aqmar Hakimi Wan Kamaruzaman - Wan Kamaruzaman, Wan Aqmar Hakimi (2020)
Big Bros Chicken is founded by Aqmar Hakimi. The business focus on chicken dishes as people around the world have favored it as they consume tons of chicken each month. The restaurant is in Machang, Kelantan. On 8 September 2019, this restaurant began operation. A business plan is designed for the owner of the property to help him run his company efficiently and that the company is well managed. It was a dream for the owner to open branches for his business and expand its franchises nationwide. This is because he wants to share his happiness with everyone who enjoys their favorite meals with others. The process of planning all the resources efficiently, organized the resources effectively, leading then controlling the resources are being done by all administrative personnel to smooth out the business flow. Every person has their own tasks and responsibilities that have been distributed according to their work field. Big Bros chicken has taken measures to implement the Mass-Marketing approach by evading and treating all the different parts of the market as a whole, in order to ensure that marketing campaigns meet the consumer needs and wants in line with their competitiveness. It is like making all people one commodity, regardless of ethnicity, age, and gender. However, making use of this target means more competition on the market. Kentucky Fried Chicken (KFC) and Ed’De Fried Chicken are the major competitors for the Big Bros Chicken. In operational part, the company aim to operate the business efficiently by ensuring the raw ingredients supplies are enough for a month operation and be mindful not to over buy that lead to waste. This is important to keep the company not exceeding the budget for the month. Process planning involve the identification of the step-by-step processes from beginning, the customer enters the premise to end when they leave the restaurant. Business hours and opening hours of the restaurant open from Sunday to Thursday. Closed for Friday and resume the business on Saturday. Big Bros Chicken business hour starting from 11:00 a.m to 10:00 p.m but slightly different on Saturday which is 11:00 a.m to 10:30 p.m and for operating hours for this business are from 10:00 a.m to 10:00 p.m but slightly different on Saturday which is 11:00 a.m to 10:30 p.m to make preparation before customer come to dine in. The business will take a rest or closed on every Friday.